2018
DOI: 10.1088/2058-6272/aac3d0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-vacuum helium cold plasma treatment on seed germination, plant growth and yield of oilseed rape

Abstract: The effects of low-vacuum helium cold plasma treatment on the seed germination, plant growth and yield of oilseed rape (Brassica napus L. cv. Zhongshuang 9) were investigated. Seeds were exposed to low-vacuum helium cold plasma ranging from 0-120 W for 15 s. Cold plasma increased the germination, plant growth and yield of oilseed rape, and the treatment of 100 W provided the best result. The germination rate, germination and vigor indices, and uniformity of emergence were improved by cold plasma treatment. Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 31 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…Recently, the application of cold plasma in seed germination and plant growth has been reported in crops and vegetables (Bourke et al., 2018; Ji et al., 2016; Jiang et al., 2014; Li et al., 2018). However, little research has been reported in turfgrass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the application of cold plasma in seed germination and plant growth has been reported in crops and vegetables (Bourke et al., 2018; Ji et al., 2016; Jiang et al., 2014; Li et al., 2018). However, little research has been reported in turfgrass.…”
Section: Discussionmentioning
confidence: 99%
“…Cold plasma has been successfully applied to improve the permeability, wettability, and water absorbing ability of seeds (Li et al, 2014;Li et al, 2017;Volin et al, 2000 ). It has also been used to improve α-amylase activity and seed reserve utilization efficiency to break dormancy and stimulate seed germination (Ji et al, 2016;Li et al, 2014) and to increase chlorophyll contents and photosynthetic ability to improve plant growth and crop yields (Jiang et al, 2014;Li et al, 2016;Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A field study of okra (Abelmoschus esculentus) in India, found that cold low pressure plasma seed treatment improved different agronomic attributes, including the harvesting time, 50% flowering time, flower number, fruit number and weight, and okra yield [73]. Recently, Li et al [74] reported increase in pod numbers (13.8%) and grain weight (8.2%) after priming oilseed rape plants with cold low pressure plasma at the reproduction stage. In another report, cold atmospheric pressure plasma seed priming increased the flower number (41.5%) and fresh weight (24%) in Cichorium intybus [51].…”
Section: Effects Of Plasma On Plant Vegetative Growth and Reproductionmentioning
confidence: 99%
“…Plasma treatment is a simple process in which the surface properties of a material are modified using ionized gas without impacting the bulk properties [ 28 , 29 ]. By selecting appropriate gases, desired characteristics including wettability, adhesion, and biocompatibility can be conferred on the material surface [ 30 , 31 ]. Plasma treatment can be performed in a vacuum or using atmospheric plasma [ 32 ].…”
Section: Introductionmentioning
confidence: 99%